Transformation of Differentiated Teaching Methods to Promote Critical Thinking in Primary School Pupils - Fitri Indriani; Satrianawati; Heldayanti (International Journal of Learning Reformation in Elementary Education, 2026)
This study examines how differentiated instruction is implemented in primary school classrooms and its role in fostering students’ higher-order thinking skills. Using a qualitative case study approach, data were collected through in-depth interviews, classroom observations, and document analysis involving five teachers from grades 1 to 5. The findings indicate that teachers adapt instructional strategies to address students’ readiness levels, learning profiles, and individual interests. This pedagogical transformation is reflected in the use of contextual learning, project-based activities, reflective practices, and digital resource integration. These approaches create more inclusive and responsive learning environments. As a result, students demonstrate improved analytical reasoning, evaluative thinking, and argument construction. The study underscores that differentiated instruction not only enhances student engagement but also supports meaningful learning. It concludes that this approach is essential for meeting the demands of 21st-century education and aligns closely with the principles of the Merdeka Curriculum.